The Americanness of the Social Gospel; An Inquiry in Comparative History - Hutchison, William Robert (Church history, 1975)
In an essay of the early 1920s, the Swiss theologian Emil Brunner offered alternative phrasings for the Protestant liberalism against which his generation was in revolt: one could speak of “the evolutionistic optimism of world-betterment,” or simply of “Christian Americanism.”